Bobwhite Whistling Activity and Population Density on Two Public Hunting Areas in Illinois - Jack A. Ellis; Keith P. Thomas; Paul Moore (National Quail Symposium Proceedings, 2017)
Eight years of data from 2 public hunting areas in southern Illinois demonstrate high multiple correlations (r = 0.97 and 0.84) for prebreeding densities and call indices with the prehunt densities of bobwhites (Colinus virginianus). Models derived from multiple correlation analyses produced satisfactory predictions of prehunt densities. The average number of calls per stop was the key element in the predicting model. The number of whistling cocks heard per stop is of limited value as an index because of difficulty in determining numbers when more than 7 whistling cocks are within hearing. The mod ls for the 2 areas appear different, but this possible difference cannot be satisfactorily confirmed on the basis of data for only 8 years.